The First Principle in Late Neoplatonism : A Study of the One's Causality in Proclus and Damascius - Greig, Jonathan (Philosophia Antiqua Ser, 2020)
Half Title -- Series Information -- Title Page -- Copyright Page -- Dedication -- Contents -- Acknowledgements -- Preface -- Introduction -- 1.1 The Backdrop of Causality in a Platonist/Aristotelian Context -- 1.2 Why Proclus and Damascius? -- 1.3 Reception in Byzantine, Arabic, and Latin Contexts -- 1.4 The Focus of This Study -- Chapter 1 The Background to Proclus and Damascius -- 1.1 Plotinus -- 1.1.1 The One as Anticipating Intellect's Nature -- 1.2 Porphyry -- 1.2.1 The Anonymous Parmenides Commentary -- 1.2.2 Assessing Porphyry and the Anonymous Commentary in Light of Plotinus -- 1.3 Iamblichus -- 1.4 Conclusion: Syrianus' Transformation as the Foundation for Proclus and Damascius -- Chapter 2 Proclus' Causal Framework -- 2.1 The Building Blocks of Causality in Proclus -- 2.1.1 The Cause as Greater Than Its Effect -- 2.1.2 ἐνέργεια, δύναμις, and Causal Synonymy in Proclus -- 2.1.3 Productive Causes and Two Kinds of Intermediaries -- 2.2 Unparticipated and Participated Causes -- 2.2.1 Participated Causes as Relative to Participants: Proclus' Shift from Plotinus -- 2.2.2 Relating Unparticipated Causes with Participants -- 2.3 The Derivation of Participated Entities and Lower Levels from the Unparticipated -- 2.4 Conclusion -- Chapter 3 Damascius' Causal Framework -- 3.1 Synonymy in Causal Relations -- 3.2 Causal Synonymy and Similar/Dissimilar Effects -- 3.3 Unparticipated Causality and Self-Constitution -- 3.3.1 Self-Constitution and Reversion -- 3.3.2 Unparticipated/Participated Causality -- 3.4 Conclusion -- Chapter 4 Proclus on the One's Causality -- 4.1 Proclus' Proofs for the One -- 4.1.1 et Prop. 1-4: Unity as an Ontological Component -- 4.1.2 et Prop. 5: the One as Unparticipated -- 4.1.3 et Prop. 6: the One's Causality Delegated to the Henads -- 4.1.4 Putting Proclus' One in Perspective -- 4.2 The One within Proclus' Causal Framework.